Who cares? (Ageing, Care and Migration) - Ezzeddine, Petra (Lidé města, 2014)
The Czech Republic is in the process of transforming its social system which is not capable of managing adequate care of its old citizens. In the last years we have witnessed an increase in the number of mediating agencies that import mainly Ukranian migrants for the purpose of engaging them in care work focusing on elderly people. The paper presents results of pilot ethnograpic research and focuses on commodification of care work for elderly people and the vulnerable character of domestic care work provided by Ukrainian female migrants in the Czech Republic. I argue that this specific “product” – the Ukrainian female caregiver – is based on the intersections of gender, ethnicity and migration.